(untitled) (Revista horizonte, 2022)
The transformation processes undergone in Chile consequence of modernization have brought problems related to nutrition and physical activity. These factors and bad habits such as sedentarism, have repercussions on health problems, epidemiological aspects and aspects related to the performance or learning in the school system. The challenges of national country policy are centered on the reduction of economic gaps and the achievement of equity in educational issues as promoters of social transformation. Inquiry teaching methods to improve the learning and academic performance of children becomes relevant. Research focused nutritional and physical activity aspects have separately shown their influence in studying disposition and as modifiers of neuronal chemical environments that favor cognitive processes related to learning. The articulation of variables can be helpful for the transformation process.